DWIBAHASA DALAM TUTURAN SEHARI-HARI BAHASA DAYAK KANAYATN DIALEK AHE (KAJIAN SOSIOLINGUISTIK) - Dawa Putri, Theodelind Eunike Pramesti (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This analysis aims to increase information regarding bilingual development in the Dayak Ahe language. The main topic of discussion in this research is the use of bilingualism, namely Dayak Ahe language and Indonesian among the Dayak Kanayatn tribe community in Anjongan District. carried out by people in everyday conversations. Qualitative descriptive research method with data collection techniques carried out using recording and note-taking techniques. The data analysis technique uses three stages, namely transcripts of recordings, language identification, and data conclusions. The data source in this research is the Dayak Kanayatn tribe community and the object is everyday speech. The research results found ten different speech contexts using bilingualism. Participants in bilingual speech include the family and micro-community spheres. All speech situations in conversation are informal. The use of bilingualism in society in everyday conversations follows the pattern of interlocutors, if the interlocutor uses Indonesian first, they will be responded to in Indonesian, and vice versa, if the interlocutor uses Dayak Ahe language, they will be responded to using Dayak Ahe language. The emergence of the use of bilingualism among the Dayak Kanayatn ethnic community occurs as a result of social contact so that the use of bilingualism makes it easier for each conversation to be understood by the speaker and the interlocutor.